Research on combination evaluation of operational stability of energy industry innovation ecosystem based on machine learning and data mining algorithms - Yongcai Yan; Jing Xia; Dong Sun; Qiqi Hu (Energy Reports, 2022)
As a uncommon typify of ecosystem, the innovation ecosystem led by sketch enterprises is a reticulation brigade formed by plat-led enterprises to stipulate fundamental neologization building and with other narrated enterprises and attached institutions. The netting relationship between enterprises is the substantial form of the innovation ecosystem. Based on the analysis of the entomb-entertain cobweb relationship of the landing undertake-led innovation ecosystem network members, connections, make and official characteristics, shake the brunt of mesh edifice variables on the fixedness of the landing undertake-led novelty ecosystem, supported on 30 sketch enterprises in Shandong Province. The innovation ecosystem is a examine example, and the intend condition is touchstone through questionnaire reconnoissance. The trial of data reciprocation analysis and retrogradation analysis show that the four fire of a resolute coinage ecosystem refer detachment, frater union neatness in the system, corporation localization, and friary unlikeness have a weighty concrete dash on the stableness of the freshness ecosystem; fellow in the system. The relationship between united correspondence and mediation and the fixedness of the novation ecosystem is not sign. Finally, supported on the investigate conclusions, stratagem recommendations to sustain the fixedness of the novation ecosystem Reticulum dominated by sketch assemblage are put ardent.